AIE-active theranostic system: selective staining and killing of cancer cells. Issue 3 (20th December 2016) - Gui, Chen; Zhao, Engui; Kwok, Ryan T. K.; Leung, Anakin C. S.; Lam, Jacky W. Y.; Jiang, Meijuan; Deng, Haiqin; Cai, Yuanjing; Zhang, Weijie; Su, Huifang; Tang, Ben Zhong
Abstract : A mitochondrion-specific AIEgen is a theranostic molecule, with the function of lighting up and killing cancer cells rather than normal cells. Abstract : Cancer is the leading cause of death worldwide. With the advantages of low cost, high sensitivity and ease of accessibility, fluorescence imaging has been widely used for cancer detection in the scientific field. Aggregation-induced emission luminogens (AIEgens) are a class of synthesized fluorescent probes with high brightness and photostability in the aggregate state. Herein, a new positively-charged AIEgen, abbreviated as TPE-IQ-2O, is designed and characterized. TPE-IQ-2O not only can distinguish cancer cells from normal cells with high contrast with the aid of the difference in mitochondrial membrane potential as well as the quantity of mitochondria, but it also works as a promising photosensitizer to kill cancer cells through generation of reactive oxygen species upon white light irradiation, thus making it a promising AIE theranostic system.